¿Qué significa ser LGTB en televisión estadounidense actual? estudio de cuatro personajes LGTB - Verne Ugarte, Camila Cecilia (2020)
This research seeks to observe LGBT characters created in recent years on American television that show a new type of representation for each part of the LGBT community, one that is closer to the way people identify themselves, less offensive and more diverse.